2019
DOI: 10.21834/e-bpj.v4i12.1817
|View full text |Cite
|
Sign up to set email alerts
|

Windstorm Resilient Rural Housing: Lessons learned in Temerloh, Malaysia

Abstract: In 2019 alone, Temerloh district located in central Peninsular Malaysia has been hit by unpredictable wind storms in localised areas which damaged more than 185 rural homes.  This research set out to assess the structural vulnerabilities of damaged rural houses to severe winds in Temerloh and lessons learned from windstorm damage through field surveys of damaged homes between March 2019-August 2019 and supplemented by district-level post-windstorm reconnaissance reports prepared by Malaysia Civil Defense Force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, the results ( Figure 3 ) showed that the extent of damage to the villages did not correspond entirely to the tornado intensity of the location (i.e., areas with high tornado intensity did not necessarily have more severely damaged houses). It is also commonly believed that in rural areas where the quality of housing is generally not as good as in cities, areas with a high building density may have more severe damage to houses during a tornado [ 36 ]. However, the observed damage pattern showed that the building density was not related to the severity of damage to houses (i.e., villages with a high building density were not necessarily more severely damaged during the tornado).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results ( Figure 3 ) showed that the extent of damage to the villages did not correspond entirely to the tornado intensity of the location (i.e., areas with high tornado intensity did not necessarily have more severely damaged houses). It is also commonly believed that in rural areas where the quality of housing is generally not as good as in cities, areas with a high building density may have more severe damage to houses during a tornado [ 36 ]. However, the observed damage pattern showed that the building density was not related to the severity of damage to houses (i.e., villages with a high building density were not necessarily more severely damaged during the tornado).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, kitchen houses, which are common in rural residential areas, significantly reduced the stability of the houses due to a height difference. Lam et al [ 36 ] analyzed the windstorm resilience of rural houses in the Temerloh district, Peninsular Malaysia. The study showed that high wind speed events caused severe damage to roof sheathings and non-structural components.…”
Section: Introductionmentioning
confidence: 99%